PROBLEMATIKA PERUBAHAN HAK GUNA BANGUNAN MENJADI HAK MILIK PADA KAWASAN WISATA (STUDI DI KABUPATEN LOMBOK BARAT) - ARIEF RAHMAN; WIWIEK WAHYUNINGSIH; SHINTA ANDRIYANI; DIMAN ADE MULADA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to examine and analyze the mechanism for increasing building use rights to property rights for land in the Gili Gede Sekotong tourism area, West Lombok and the obstacles faced. The type of research used in this article is normative and empirical research using the statutory regulatory approach, conceptual approach, case approach, and sociological approach.The results of the research show that the mechanism for increasing building use rights to ownership rights for land in the Gili Gede Sekotong tourist area, West Lombok, is: Submitting a written application for documents to the local National Land Office by attaching: several requirements, Submitting the application to the counter officer for research. completeness of the documents which are a requirement in the application for an increase in land rights. After the required documents are complete, then make payment for registration, measurement and land inspection fees. Carrying out measurements and inspection of the land plot, BPN follows up process of applying for an increase in building use rights to ownership rights, the applicant pays the BPHTB, and the Land Office will record the rights and issue a land certificate. The obstacle faced is that in submitting an application for an increase in rights, the applicant cannot complete the required documents for a Building Construction Permit (IMB) because even though several bungalows have been built on the land he purchased, even though the condition of the bungalows is currently in disrepair, this has not been followed up by obtaining a building construction permit ( IMB), so that when applying for an increase in file rights the document is rejected because it does not have an IMB as one of the conditions that must be met and is a cost factor.